Antyk w Kronice Polskiej Anonima tzw. Galla i w Translacji św. Mikołaja tzw. mnicha z Lido jako problem badawczy - Skibiński, Edward (Studia Europaea Gnesnensia, 2012)
In the article, i examine the theoretical and practical possibilities of comparative analysis of Latin medieval texts. Such analysis should enable them to be situated in the context of their contemporary writings and the texts from earlier periods which featured on their literary horizon.